Penguatan Kapasitas dan Peran Tenaga Kesehatan Berbasis Komunitas dalam Implementasi G1R1J di Puskesmas Kota Ende - Kopong, Pius; Krispina Owa; Syaputra Artama (Mitra Akademia: Jurnal Pengabdian Masyarakat, 2025)
Dengue Hemorrhagic Fever (DHF) remains a significant public health issue in Indonesia, including in the working area of Puskesmas Kota Ende, which has reported high case numbers over the past five years. The national strategy "One House, One Larvae Monitoring Officer" (G1R1J) has not yet achieved optimal results, largely due to limited health worker involvement in education, monitoring, and community support. This community service initiative seeks to strengthen health workers’ capacity through participatory training consisting of three sessions: deepening DHF knowledge, structuring G1R1J implementation, and practicing larvae surveillance and health education at the household level. Methods included interactive lectures, simulations, discussions, and fieldwork. Evaluation showed marked improvements in knowledge 44% to 86.7% (session 1), 8% to 82.7% (session 2), and 22% to 88% (session 3). Besides cognitive gains, the program also developed soft skills, making participants more communicative, collaborative, and responsive to local dynamics. These results indicate that participatory training effectively enhances technical and interpersonal competencies, positioning health workers as key agents of behavioral change in dengue prevention. This model holds potential for replication in other regions facing similar dengue challenges.. Keywords: Empowerment, Health Workers, Implementation, G1R1J